A SYSTEMATIC LITERATURE REVIEW OF FACTORS INFLUENCING SOCIAL ENTREPRENEURIAL INTENTIONS - Shih-Yee Loh; Jeffrey Cheah (Journal of Islamic, Social, Economics and Development, 2022)
Social entrepreneurship movement has proven its efficiency in addressing world pressing social issues immediately upon creating economic value. However, social enterprise development in many countries, including Malaysia, is still at the infancy stage. This paper designed to identify and conceptually structure the most prominent factors that influence the social entrepreneurial intentions, based on the systematic review process, content analysis and gap analysis approaches. Specifically, from 967 records derived from renowned scholarly database Scopus, this study deliberately stipulated 17 core empirical literature, inspected with in-depth content analysis to identify the most prevalence constructs employed by previous researchers, and mapped their statistical findings by gap analysis approach. Subsequently, grounded on the Theory of Planned Behaviour, a conceptual framework that posits social entrepreneurial intention, which comprises of perceived social support, moral obligation, selfefficacy, empathy and social worth, was established. The research findings deliberately contribute to social enterprise literature in a developing country context which remains limited, offers a guideline to a relevant legal agency in enhancing the social enterprise ecosystem, and provide a practical reference to future research by disclosing the research gaps and a readymade model for empirical research.